Tempora mutantur, nos et mutamur in illis: Religion and Female Employment over Time - Justina A.V. Fischer; Francesco Pastore (Institute for the Study of Labor (IZA), 2015)
This study analyses whether the role of religion for employment of married women in Europe has changed over time and along women's life cycles. Using information on 44'000 married European women from the World Values Survey 1981-2013, we find that in OECD-Europe there is little difference among women of any age since 1997. For non-OECD-Europe, we find differences by religion among young women, but not among those older than 40 years, which we attribute to an upbringing under communist regimes. Only Muslim women show a lower employment probability that persists across time, regions, and life cycles.
Keywords: D83; J16; J22; N34; Z12; Z13; 330; religion; labor market participation; modernization; gender; Europe; transition countries; Eastern Europe; OECD; World Values Survey